New trends in CO activation - Guczi, L., 1932- (Studies in surface science and catalysis, 1991)
The aim of this volume is to provide scientists with a comprehensive summary of new research areas in the activation of carbon monoxide, as one of the most reactive molecules, and in its applications. In order to understand the variety of the reactivity of CO, a quantum-chemical approach helps the reader to understand the binding state of CO to the solid surface (Chapter 1). The structure of the adsorbed CO can be better understood by examining its reactivity towards single crystals in the absence and in the presence of promoters (Chapter 2). The first approach in the reactivity study is that of studying catalytic activity of single crystals and structure sensitivity which are summarized in Chapter 3. One of the most prominent effects in the CO activation process is ascribed to the presence of additives, promoters which, in a real catalyst system, are far more complicated than on single crystal surfaces (Chapter 4). The original Fischer-Tropsch process applied fused iron or cobalt catalysts which were suitable for producing mainly straight chain hydrocarbons. The two most important processes involving CO activation, the new FT process and alcohol formation are discussed in Chapters 5 and 7. An important type of catalyst, the bimetallic catalysts, is discussed in Chapter 6. The role of hydrogen as one of the most frequently used partners in CO activation is discussed in Chapter 8. The field of production of specialty chemicals is an excellent example of the homogeneous catalytic activation of CO (Chapter 9). In Chapter 10 an overview is given of the industrial applications of CO chemistry and these are illustrated by working processes. The final chapter gives the reader some hints about future progress in the field.